New Iterative Method with Application - Ababneh , O.; Zomot, N. (JOURNAL OF ADVANCES IN MATHEMATICS, 2021)
In this paper, we consider iterative methods to find a simple root of a nonlinear equation f(x) = 0, where f : D∈R→R for an open interval D is a scalar function.